2015
DOI: 10.1007/s00253-015-6707-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of phenazine 1,6-di-carboxylic acid from Pseudomonas aeruginosa strain HRW.1-S3 and its role in biofilm-mediated crude oil degradation and cytotoxicity against bacterial and cancer cells

Abstract: Pseudomonas sp. has long been known for production of a wide range of secondary metabolites during late exponential and stationary phases of growth. Phenazine derivatives constitute a large group of secondary metabolites produced by microorganisms including Pseudomonas sp. Phenazine 1,6-di-carboxylic acid (PDC) is one of such metabolites and has been debated for its origin from Pseudomonas sp. The present study describes purification and characterization of PDC isolated from culture of a natural isolate of Pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 45 publications
(63 reference statements)
1
28
1
Order By: Relevance
“…The PDC phenazine was first isolated from Streptomyces species; it was demonstrated to be the potential agent for controlling metabolism and biofilm formation in Candida albicans [ 49 , 50 ]. Compared to other phenazine metabolites, PDC showed a substantially broader spectrum of cytotoxicity effect towards a number of cancer cells of different origins, including HT29, HeLa, and MCF7 cell lines, with less activity on DU145 (Human prostate cancer cell lines) [ 51 ].…”
Section: Bacteria As Anti-cancer Agents Through Released Substancesmentioning
confidence: 99%
“…The PDC phenazine was first isolated from Streptomyces species; it was demonstrated to be the potential agent for controlling metabolism and biofilm formation in Candida albicans [ 49 , 50 ]. Compared to other phenazine metabolites, PDC showed a substantially broader spectrum of cytotoxicity effect towards a number of cancer cells of different origins, including HT29, HeLa, and MCF7 cell lines, with less activity on DU145 (Human prostate cancer cell lines) [ 51 ].…”
Section: Bacteria As Anti-cancer Agents Through Released Substancesmentioning
confidence: 99%
“…Indeed, PDC was mostly identified from Streptomyces species (Wang et al, 2011;Remali et al, 2017). PDC had not been widely discussed in the context of Pseudomonas until recently; researchers found that mutation of the phzA gene in Pseudomonas chlororaphis HT66 resulted in a significant increase in PDC production, which distinguishes the phenazine pathway producing only PCA from the pathway forming both PCA and PDC (Dasgupta et al, 2015;Guo et al, 2017; Figure 9). Another study reported the production of PDC in the genetically engineered strain Pseudomonas chlororaphis GP72ANlphzG (Guo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The phenazines are small molecules that can penetrate different types of cells, including prokaryotes. Many phenazines present antimicrobial activity, suppressing pathogenic microorganisms of humans, animals and plants, also playing an important role in the survival strategies of bacteria in the environment (Chen et al, 2014 ; Briard et al, 2015 ; Dasgupta et al, 2015 ; Garrison et al, 2016 ; Morrison et al, 2016 ). The P. aeruginosa LV strain is a great producer of phenazine carboxylic acid (PCA).…”
Section: Discussionmentioning
confidence: 99%